THE ROLE OF DEPOSITION RATE ON THE ELECTRICAL CONDUCTIVITY AND ENERGY GAP OF (a–Ge) THIN FILM - Al-Essa, Izzat M; Hamadi, Talib Saloom (Al-Nahrain Journal of Science, 2018)
The films of amorphous germanium (a–Ge) were prepared by evaporation under high vacuum conditions (10-6) torr. The influence of various deposition rates within the range(2 – 10)Ǻ/sec on the dc electrical conductivity (σRT) and energy gap (Eg). The temperature dependence of conductivity for various deposition rates recorded in the range (303 – 503)K consist of two conduction regions within the temperature range (303–413)K and (413–503)K. From the absorbance spectrum Eg (energy gap) were obtained according to Tauce formula. It is found that Eg decreases from 1.08eV to 0.91eV when the rate of deposition increase from (2 – 10) Ǻ/sec while the electrical conductivity (σRT) increases from 1.28×10ֿ 4(Ώ.cm)ֿ ¹ to 11.53 ×10ֿ 4(Ώ.cm)-1 respectively.